Clinicopathological pattern of oestrogen receptor, progesterone receptor and human epidermal growth factor receptor-2 over-expression of epithelial ovarian carcinomas in Nigeria (2023)
Background: Ovarian cancer is the leading cause of death from all gynaecological malignancies. Only few biomarkers of epi thelial ovarian cancer (EOC) prognosis have been studied so far among Nigerian patients. Objective: To determine the pattern of oestrogen receptor (ER), progesterone receptor (PR) and human epidermal growth factor receptor 2 (HER-2) expression in patients with EOC seen in Nigeria Materials and Methods: This was a retrospective multicentre study of 102 cases of epithelial ovarian cancers. Relevant clinical information was obtained from hospital-based records in the 3 participating centres. Tissue microarrays were constructed using representative tumour tissue and the ER, PR and HER2 immunohistochemical staining was carried out at the University of Chicago, United States of America. Results: Serous carcinomas predominated (71% of cases). ER positivity was observed in 31.4%, PR positivity in 21.5% and HER2/neu in 16.7% of tumours. Fifty-two percent of tumours were triple negative. Serous tumours were significantly asso ciated with ER positivity (p=0.001). Mean patient age for EOC was 52.6 ± 13.1 years. There were no statistically significant associations between hormone receptor status and histological grade, FIGO staging or survival. Conclusion: Serous tumours were significantly associated with ER expression while non-serous tumours tended to be triple negative.